Using non-commutative monoids for construct three-party key establishment - Han, Song; Chang, Elizabeth; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Three-party key establishment protocol can help three participants to establish a shared secret key through interactions via public channels. In this paper, a novel three-party key agreement protocol is proposed. The protocol is based on non-commutative monoids in mathematics. It is a generic construction and one-time protocol per key establishment.